2020
DOI: 10.1186/s42077-020-00084-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of job satisfaction, work-related strain, and perceived stress in nurses working in different departments in the same hospital: a survey study

Abstract: Objective We aimed to evaluate whether working at ICU, inpatient services, or the operating room creates differences in job satisfaction (JS), work-related strain (WRS), and perceived stress (PS) of nurses. Research methodology The study data were collected through face-to-face interviews. The data collection tools utilized in the study included a questionnaire form consisting of 19 questions. Work-Related Strain Inventory (WRSI), S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Among the studied sample, work‐related stress was above average and higher than the score found by both Pekince and Aslan ( 2020 ) who reported a mean WRS of 41.18 ± 2.68 and Erdoğan et al ( 2020 ) who reported a mean of 38.85 ± 5.76. These studies were conducted in Turkey before the COVID‐19 pandemic.…”
Section: Discussioncontrasting
confidence: 58%
“…Among the studied sample, work‐related stress was above average and higher than the score found by both Pekince and Aslan ( 2020 ) who reported a mean WRS of 41.18 ± 2.68 and Erdoğan et al ( 2020 ) who reported a mean of 38.85 ± 5.76. These studies were conducted in Turkey before the COVID‐19 pandemic.…”
Section: Discussioncontrasting
confidence: 58%
“…In a study conducted among nurses, it was found that the WRSI was reported to have an average score of 38.85 ± 5.76 points. 15 Factors such as quarantine periods spent away from family, fear of contagion, and night shifts may have been effective in the higher WRSI average as we determined. In our study, it was also observed that those at risk for anxiety or depression had higher work-related tension scores than those who did not.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, our findings align with a study conducted in the USA, where a substantial group of Certified Registered Nurse Anesthetists was surveyed regarding their occupational exposure to inhalational anesthetic agents, yielding quite similar results ( 5 ). The study demonstrated that exposure to waste anesthesia gases contributes to fatigue ( 9 , 17 ). Anesthetic gas pollution can arise from various sources, including anesthesia breathing circuits like pediatric T-piece circuits, especially in the absence of a proper scavenging system and the maintenance of the operating theatre ventilation system ( 5 ).…”
Section: Discussionmentioning
confidence: 99%